Structural characterization of polyamine utilization enzymes in Pseudomonas aeruginosa - Yap, Shao Quan (Nanyang Technological University, 2025)
Polyamines are essential for cellular functions such as protein translation and cell proliferation, as well as bacterial pathogenicity. However, excess polyamine levels also affect cell viability, presenting an opportunity to target pathogens such as Pseudomonas aeruginosa by disrupting homeostasis and maintaining high polyamine levels. Pseudomonas aeruginosa maintains polyamine homeostasis through biosynthesis, uptake, and catabolism mediated by spuABCDEFGH operon. Evidence suggests catabolism by SpuABC enzymes occurs via γ-glutamylation pathway and is specific to spermidine. While these enzymes are potential targets for disrupting polyamine catabolism, structural elucidation is necessary to fully understand their mechanisms. In this thesis work, SpuA, SpuB, and SpuC were successfully expressed and purified, demonstrating that each exists natively as a dimer without forming a multi-enzyme complex. While SpuA and SpuC consist of identical monomers, SpuB monomers appear non-identical, suggesting possible post-translational modifications. Additionally, SpuB may belong to a distinct class of glutamine synthetases with different γ-glutamylation mechanisms, as it differs structurally from typical bacterial glutamine synthetases, which are dodecamers. These preliminary findings could pave the way towards understanding their catalytic mechanisms and intermediate states during chemical conversion, which are useful for developing inhibitors to block their activity and maintain high spermidine levels that are detrimental to the cell.